PERKEMBANGAN EMBRIO DAN LARVA IKAN PATIN NASUTUS (Pangasius nasutus Bleeker, 1863) (Pangasiidae; Pisces) - Bambang Iswanto; Evi Tahapari (BERITA BIOLOGI, 2013)
Patin nasutus (Pangasius nasutus Bleeker, 1863) (Pangasiidae; Pisces) is a potential pangasiid catfish species to be cultured in Indonesia.Many efforts has been done to explore the potency of P.nasutus for aquaculture purposes.However, basic knowledge is still very rare such as its embryonic and larval development.The present study aimed to understand the embryonic and larval development of P. nasutus resulted from induced spawning of P.nasutus brooders at Research Institute for Fish Breeding, Sukamandi. Those embryonic and larval development were observed microscopically.The results showed that diameter of the ovulated oocytes ranged 1.40-1.65 mm and fertilized eggs ranged 1.90-2.15 mm.The embryogenesis consisted of several stages as follow: morula, blastula, gastrula, organ developments and newly hatched larvae occured within periods of (minutes) 20-200, 190-220, 210-660, 600-1,140 and 1,800-2,160 after fertilization at water temperature of 28-29oC. Total length of the newly hatched larvae ranged 4.80-5.10 mm with anterior, posterior and dorsal parts of the yolk sac coloured black pigmentation. On caudal peduncle, the black spot existed since 36 hours after hatching was a strong character for P.nasutus larvae.Volume of the yolk sac was 2.65±0.14 mm3, for which 50% absorbed at 36 hours after hatching and relative fully absorbed at 78 hours after hatching. The larvae have complete morphology as adult after seven days. During early developmental stage, larvae showed cannibalism since the third day, corresponding to the first exogenous feeding.